2018
DOI: 10.3389/fpsyg.2018.02164
|View full text |Cite
|
Sign up to set email alerts
|

Insight and Dissociation in Lucid Dreaming and Psychosis

Abstract: Dreams and psychosis share several important features regarding symptoms and underlying neurobiology, which is helpful in constructing a testable model of, for example, schizophrenia and delirium. The purpose of the present communication is to discuss two major concepts in dreaming and psychosis that have received much attention in the recent literature: insight and dissociation. Both phenomena are considered functions of higher order consciousness because they involve metacognition in the form of reflective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 94 publications
1
31
0
1
Order By: Relevance
“…In addition to this, future work could also control for psychiatric disorder. This is important because conditions such as psychosis can effect lucid dreaming (Mota et al, 2016;Voss et al, 2018) and predisposition to fantasy proneness and delusional beliefs (Tan et al, 2019). Moreover, these variables correlate positively with belief in the paranormal (Irwin et al, 2012a,b).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, future work could also control for psychiatric disorder. This is important because conditions such as psychosis can effect lucid dreaming (Mota et al, 2016;Voss et al, 2018) and predisposition to fantasy proneness and delusional beliefs (Tan et al, 2019). Moreover, these variables correlate positively with belief in the paranormal (Irwin et al, 2012a,b).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…A central characteristic is that experiencers are typically able to signal their lucid state during dream periods using preagreed eye-movement signals (LaBerge, 1980;LaBerge et al, 2018). Concomitantly, lucid dreaming possesses consciousnessrelated features such as access to waking memories, increased insight and control, positive affect, body dissociation, and logical thought (LaBerge et al, 1981;Voss et al, 2009Voss et al, , 2018. Other criteria used to distinguish lucid dreams are memory of the waking state, sentience of freedom of decision, and full intellectual abilities (Tholey and Utecht, 1987;Lee, 2017).…”
Section: Introduction Lucid Dreaming Backgroundmentioning
confidence: 99%
“…35 However, the 32 Dawes et al (2020) and Zeman (correspondence). 33 Voss et al (2018); Windt and Voss (2018) Saunders et al (2016) include recent meta-analyses and summaries of this work. Here, lucid dreams are characterised by the three dissociable features : (i) the presence of subject insight (a conscious awareness that one is dreaming) (ii) control (manipulation of dream content and narrative) and dissociation from one's dream experience (such as seeing the dream as if it were playing on a screen, or viewing one's self from the outside).…”
Section: Aphantasia and Lucid Dreaming: A Testable Empirical Hypothesismentioning
confidence: 99%
“…116-117). See footnote 28 for a discussion of lucid dreaming and the inactive account of dreaming which involves the hypothesis that lucid dreaming is a hybrid phenomenon (Voss et al 2018;Soteriou 2017). 35 Zeman (correspondence).…”
Section: Aphantasia and Lucid Dreaming: A Testable Empirical Hypothesismentioning
confidence: 99%
“…In fact, there is also a continuity of insight function between wake and dream state. Neuroimaging and electroencephalogram (EEG) research showed that the frontal areas of the brain, which are related to psychotic insight, are highly activated in LD (Dresler et al, 2015;Voss et al, 2018). To some extent, LD can be seen as a model for insight into the psychotic state.…”
Section: Introductionmentioning
confidence: 99%